Stone-free Rate of Ultrasound-assisted and Fluoroscopy-guided Extracorporeal Shockwave Lithotripsy for Radiopaque Renal Stones - Khan, Muhammad Nawaz; Hassaan ul Hassan,; Haneef, Faisal; Jafri, Abbas; Saad, Hafiz Muhammad; Kumar, Sanjeet; Syed Rabiullah,; Gazder, Tanzeel (Indus Journal of Bioscience Research, 2024)
Background: Extracorporeal shock wave lithotripsy (ESWL) has been a widely accepted method for treating urinary stones since the early 1980s. ESWL is the preferred non-invasive treatment for renal stones that are smaller than 1.5 cm. Ultrasound and fluoroscopy are used during ESWL operations to visualize the fragmentation. Objective: To determine the Stone-free rate of ultrasound-assisted and fluoroscopy-guided extracorporeal shockwave lithotripsy for radiopaque renal stones. Methodology: A prospective cohort study was conducted at the Sindh Institute of Urology and Transplantation from 25th February to 25th August 2022, including 75 participants per group with renal stones